2010
DOI: 10.1080/15567240802533500
|View full text |Cite
|
Sign up to set email alerts
|

Energy and Water Use in Arizona Agriculture

Abstract: Increasing energy and water concerns in Arizona are the driving forces to improve the efficiency of agricultural production within the state. In this article we address the energy and water uses in growing a variety of crops in Arizona. The goal of the research project is to identify and quantify all energy and water uses from the production of the initial seed, through the treatments of the soil and various chemical introductions, all the way until the crop is harvested in the field. Thus, the analysis is "fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Using an estimate of 1037 kilowatt-hours (kWh) per acre foot pumped [ 12 ], a conversion factor of 3600 kilojoules per kWh, the average estimate of water use calculated previously, and the estimated average yield value for conventional lettuce, an average estimate of energy use for the pumping of irrigation water was computed in units of kJ/kg/y.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using an estimate of 1037 kilowatt-hours (kWh) per acre foot pumped [ 12 ], a conversion factor of 3600 kilojoules per kWh, the average estimate of water use calculated previously, and the estimated average yield value for conventional lettuce, an average estimate of energy use for the pumping of irrigation water was computed in units of kJ/kg/y.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding conventional lettuce production, in 2001, the University of Arizona Cooperative Extension developed county-specific crop budgets estimating the operating and ownership costs of producing vegetables in Arizona using representative cropping operations and such resource inputs as water, fuel, and fertilizer [ 11 ]. Realizing that the water and energy use for agriculture is substantial, Ackers et al (2008) [ 12 ] performed an “order of magnitude” study and determined a reasonable range of estimates for resources used in the production of Arizona agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Fuel is also required for land preparation and growing operations. A recent study on energy use in growing food in Arizona found embodied energy from "seed to farm edge" in cabbage to range from 9054 to 12,061 kcal/head while in head lettuce it ranges from 6488 to 7877 kcal/head [38]. These estimates were based on calculation of energy use in each farm operation (including on-farm machine use and irrigation) obtained from the AZ Crop Budget tables prepared by University of Arizona Cooperative Extension.…”
Section: Energy-foodmentioning
confidence: 99%